Assessment of transport and isolation methods for gonococci. Issue 6 (December 1980) - Taylor, E; Phillips, I
Abstract : Urethral discharge from men was diluted to give heavy and light inocula and cultured on seven different solid culture media, including two transport/isolation media, or held in three types of semi-solid transport medium for varying periods and then cultured. The amount of growth was quantitated and the performance of the different systems compared. Fresh non-selective media were best, with up to two failures in 254 cultures on each medium. With selective media there were 9-23 failures with heavy inocula and 22-47 failures with dilute inocula. For Transgrow or the Jembec system incubation before holding at ambient temperature was better than holding followed by incubation. Transport media yielded good results if cultures were set up within six hours; only minor losses occurred after 24 hours.